1988
DOI: 10.1111/j.1751-1097.1988.tb08835.x
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Singlet Molecular Oxygen by Thiols and Related Compounds, Possible Protectors Against Skin Photosensitivity

Abstract: From time-resolved measurements of the decay of singlet molecular oxygen phosphorescence at 1270 nm in D,O, direct estimates have been gained for the rate constants of the singlet oxygen reactions with a group of sulphur compounds in the pD range 5 to 13. In the case of most of the thiols, the results are consistent with singlet oxygen reacting exclusively with the thiolate anions. At the normal physiological pH 7, the apparent rate constants (in units of M-' s-') were 8.9 x loh (cysteine), 2.5 x lo6 (N-acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 28 publications
9
79
1
1
Order By: Relevance
“…Therefore, glutathione at cellular concentrations does not appear sufficiently reactive with singlet oxygen to afford the cells protection, regardless of its location. This observation is consistent with the bimolecular rate constants observed for the reaction of glutathione with singlet oxygen (25). Further Figure 4 illustrates a model of the effect of the cell wall structure on singlet oxygen toxicity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, glutathione at cellular concentrations does not appear sufficiently reactive with singlet oxygen to afford the cells protection, regardless of its location. This observation is consistent with the bimolecular rate constants observed for the reaction of glutathione with singlet oxygen (25). Further Figure 4 illustrates a model of the effect of the cell wall structure on singlet oxygen toxicity.…”
Section: Discussionsupporting
confidence: 76%
“…These authors also report that small peptides react at essentially the same rate as do their constituent amino acids, which implies that glutathione should react with singlet oxygen. Rougee and co-workers (25) have demonstrated that the bimolecular rate constants for glutathione and cysteine reactions with singlet oxygen are in fact similar. Glutathione must therefore be considered a potential protective agent against killing of bacteria by singlet oxygen.…”
mentioning
confidence: 99%
“…In contrast, no cleavage was observed when DNA was incubated with AGE protein in the absence of irradiation or when irradiation was performed in the absence of sensitizer protein. Importantly, AGE sensitization of DNA damage was shown to proceed equally well under aerobic and nonaerobic conditions, and thus antioxidants such as catalase and superoxide dismutase had little effect on DNA cleavage by AGE sensitization, whereas excited state quenchers such as NaN 3 , KI, and organic thiol compounds were strongly protective when present during irradiation, either in the absence or presence of oxygen (Rougee et al, 1988;Beutner et al, 2000). Based on these earlier findings, DNA protection from AGE photosensitization by test compounds present during irradiation was used as a broad initial screen for the identification of agents capable of interfering with sensitized photodamage by mechanisms different from antioxidant or UV screening activity.…”
Section: Qpes Screen 1: Suppression Of Age-photosensitized Dna Damagementioning
confidence: 99%
“…Ergothioneine also interacts with ROS, most probably through the quenching of singlet oxygen (Hartman et al, 1988). In addition, the compound reacts with hydroxyl radicals (Rougee et al, 1988;Akanmu et al, 1991), and scavenges hypochlorous acid (Akanmu et al, 1991), peroxyl radical (Asmus et al, 1996), and peroxynitrite (Aruoma et al, 1997). The effects of ergothioneine on oxidative and/or antioxidant enzymes are largely unexplored.…”
Section: Ergothioneine Protects Endothelial Cellsmentioning
confidence: 99%